Correlations of azimuthal anisotropy Fourier harmonics with subevent cumulants in pPb collisions at √sNN=8.16TeV; Physical Review C; Vol. 103, iss. 1 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Babaev A. A. Anton Anatoljevich; Baydali S. A. Sergey Anatolievich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen